2007
DOI: 10.1038/sj.onc.1210543
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine kinase Abl is required for Src-transforming activity in mouse fibroblasts and human breast cancer cells

Abstract: The cytoplasmic tyrosine kinase Src has been implicated in signal transduction induced by growth factors and integrins. Src also shows oncogenic activity when deregulated. Accumulating evidence indicates that the tyrosine kinase Abl is an important substrate for Src signalling in normal cells. Here we show that Abl is also required for Src-induced transformation of mouse fibroblasts. Abl does not mediate tyrosine phosphorylation of Stat3 and Shc, two important regulators of Src oncogenic activity. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 43 publications
5
57
0
Order By: Relevance
“…We first confirmed that the Csk substrates SFK have important roles in transforming properties of CRC cells; specifically, anchorage-independent growth and invasion were inhibited by treatment with the SFK pharmacological inhibitor, SU6656 ( Figure 2a). Similar results were obtained in MCF7 and ZR75.1 ER þ breast cancer cells (Figure 2a), which is in agreement with an important role for SFK in ER oncogenic signalling (Ishizawar et al, 2004;Sirvent et al, 2007). In contrast, the SFK inhibitor had no effect on HER2 þ breast cancer cells, SKBR3 and BT474, indicating that SFK do not have a role in every breast cancer cell ( (Sirvent et al, 2007) and not shown).…”
Section: Csk Inhibition Does Not Affect Sfk Oncogenic Activity In Crcsupporting
confidence: 87%
See 3 more Smart Citations
“…We first confirmed that the Csk substrates SFK have important roles in transforming properties of CRC cells; specifically, anchorage-independent growth and invasion were inhibited by treatment with the SFK pharmacological inhibitor, SU6656 ( Figure 2a). Similar results were obtained in MCF7 and ZR75.1 ER þ breast cancer cells (Figure 2a), which is in agreement with an important role for SFK in ER oncogenic signalling (Ishizawar et al, 2004;Sirvent et al, 2007). In contrast, the SFK inhibitor had no effect on HER2 þ breast cancer cells, SKBR3 and BT474, indicating that SFK do not have a role in every breast cancer cell ( (Sirvent et al, 2007) and not shown).…”
Section: Csk Inhibition Does Not Affect Sfk Oncogenic Activity In Crcsupporting
confidence: 87%
“…Similar results were obtained in MCF7 and ZR75.1 ER þ breast cancer cells (Figure 2a), which is in agreement with an important role for SFK in ER oncogenic signalling (Ishizawar et al, 2004;Sirvent et al, 2007). In contrast, the SFK inhibitor had no effect on HER2 þ breast cancer cells, SKBR3 and BT474, indicating that SFK do not have a role in every breast cancer cell ( (Sirvent et al, 2007) and not shown). Owing to the important function of SFK in CRC cells, we next investigated the role of Csk in the growth and invasion of CRC cells.…”
Section: Csk Inhibition Does Not Affect Sfk Oncogenic Activity In Crcsupporting
confidence: 87%
See 2 more Smart Citations
“…Abl as a downstream target of Src in breast cancer is supported by a recent study that shows that a decrease of Src kinase by a known Src inhibitor leads to a decrease of Abl kinase human breast cancer cell lines (Sirvent et al, 2007). Sirvent et al (2007) further show that Abl is involved in a Src/Abl/Rac/JNK/STAT3 signaling cascade that is important in cell transformation.…”
Section: Activated C-abl In Human Breast Cancermentioning
confidence: 57%